Circulating level of growth-differentiation factor 15 and the functional outcome after acute ischemic stroke: a systematic review and meta-analysis - Yulang Wu; Yude Wei; Jinrong He; Fengkun Zhou (Head & Face Medicine)
Abstract Growth-differentiation factor 15 (GDF-15) is a cytokine involved in cellular stress responses and inflammation. This meta-analysis evaluates the association between circulating GDF-15 levels and functional outcomes in patients with acute ischemic stroke (AIS). A comprehensive search of Medline, Web of Science, Embase, Wanfang, and CNKI was conducted up to July 15, 2024. Observational studies with longitudinal follow-up that measured GDF-15 levels within 24 h of stroke onset and reported functional outcomes, defined as a modified Rankin Scale (mRS) score of ≥ 2, were included. Odds ratios (OR) with 95% confidence intervals (CI) were used to quantify associations. Heterogeneity was evaluated using I² statistics, and a random-effects model was used to pool the results by incorporating the influence of heterogeneity. Ten studies involving 4,231 patients were included. The pooled OR indicated that high circulating GDF-15 levels were associated with a significantly higher risk of poor functional outcomes at 3 months (OR: 2.60, 95% CI: 1.95 to 3.46, p < 0.001). Sensitivity analyses by excluding one study at a time did not significantly change the results. Subgroup analyses revealed stronger associations in studies with GDF-15 cutoff values < 1200 ng/L as compared to ≥ 1200 ng/L, and in those defining poor outcomes as mRS ≥ 3 as compared to those ≥ 2. In conclusion, elevated circulating GDF-15 levels are associated with worse functional outcomes following AIS. These findings support the potential use of GDF-15 as a prognostic biomarker in stroke patients. Further research is warranted to confirm these results and explore clinical applications.